STUDY OF THE EFFICIENCY OF FERRUM IONS REMOVAL BY AQUATIC HIGHER PLANTS - Sabliy, Larysa; Konontsev, Sergii; Korenchuk, Mykola; Koltysheva, Dina (Scientific Works of Vinnytsia National Technical University, 2018)
During aerobic biological treatment of paper mill waste water, the complete treatment of sewage from ferrum ions to the indices of MPC is not provided. Traditional physical-and-chemical treatment technologies are connected with the usage of high-cost, nonrenewable sorbents, which, after treatment, form precipitation which is difficult or impossible to process. Promising alternative is the usage of aquatic higher plants, in particular, Lemna minor (duckweed). In modern research, studying the processes of ferrum ions removal, high level of their elimination is achieved only in 4 – 5 days and is 80±5. The task of reducing the duration of the treatment process is very urgent. The purpose of this work is to determine the rational parameters of the biological treatment of paper mill wastewater applying the method of active silt (COD, duration of the contact)and study the dynamics of ferrum ions removal in the process of assimilation by Lemna minor (duckweed) (by the duration of the contact and planting density). Studies were carried out on sewage waters, samples of which were selected at the wastewater treatment plant of the paper mill after the primary sedimentation tanks. Active silt from aeration station was used for aerobic treatment of waste water. Physical simulation was carried out on a pilot plant of SBR reactor type. Ferrum removal was carried out using Lemna minor, in the process of the advanced waste water treatment. Studies of ferrum ions removal dynamics were continued, using test solutions prepared from distilled water with the addition of ferric sulfate. The obtained results demonstrate regular increase of ferrum ions removal effect at the increase of planting density. The highest efficiency during the first day of the experiment of 88.5% is obtained if the planting density is approximately 5.8g/dm2, where as the lowest efficiency of 49%, if the planting density is approximately 2.9 g/dm2. Comparison of the efficiency of sewage and test solutions treatment showed no significant difference, so the presence of pollutants, stipulating the COD index in these conditions does not have a clearly expressed impact on the process of ferrum ions removal. The increase of the planting density significantly influences the intensity of the process, and can be used as the mechanism for reducing the duration of ferrum ions removal from the water.